Q&A: Participating in the telecom policy dialogue - Jensen, Mike (Technical Centre for Agricultural and Rural Cooperation, 2004)
Mike Jensen has been promoting ICTs for development for more than 15 years, and has probably seen it all. In the early 1990s he travelled around Africa helping NGOs install their first store-and-forward email systems, which were supported by APC/Gr